Installation of a New Electron Cyclotron Plasma Enhanced Chemical Vapour Deposition (ECR-PECVD) Reactor and a Preliminary Study ofThin Film Depositions - Dabkowski, Ryszard P. (My University, 2012)
A new electron cyclotron plasma enhanced chemical vapour deposition (ECR-PECVD) reactor has been installed and tested at McMaster University. The focus of this project was the installation of the reactor and the growth of silicon oxide, silicon oxynitride, cerium doped silicon oxynitride and aluminium doped silicon oxide films to test the capabilities of the reactor. Silicon oxide films were prepared with near-stoichiometric compositions and silicon rich compositions. Good repeatability of the growths was seen. An increase in deposition temperature showed stable refractive index and a decrease in the growth rates. Silicon oxynitride films of varying compositions were prepared, and showed a non-uniformity of ~1% and growth rates of ~3.5 nm/min. Films prepared with a low oxygen flow were seen to be nitrogen rich. Although the depositions using Ce(TMHD)4 showed significant cerium incorporation, there was also high carbon contamination. One likely cause of this is the high sublimator temperature used during depositions or a thermal shock to the precursor during initial system calibration. A definitive cause of the carbon contamination has not been established. The cerium films showed strong blue luminescence after post-deposition annealing in N2 above 900° C. A drop in the luminescence was observed at 1100° C and a return of the luminescence at 1200° C. Generally, high cerium incorporation was associated with higher total luminescence. Al(THMD)3 was evaluated as an aluminium precursor for Al-doped silicon oxide films. The films showed aluminium content up to 6% demonstrating the viability of using Al(THMD)3 as a Al doping precursor.
Keywords: ECR-PECVD; Chemical Vapor Deposition; Silicon Photonics; Thin Films; Cerium; Aluminum; Condensed Matter Physics; Engineering Physics; Nanoscience and Nanotechnology; Other Engineering; Other Physics; Plasma and Beam Physics; Semiconductor and Optical Materials; Condensed Matter Physics